If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + 3j = 2j Solving -4 + 3j = 2j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-2j' to each side of the equation. -4 + 3j + -2j = 2j + -2j Combine like terms: 3j + -2j = 1j -4 + 1j = 2j + -2j Combine like terms: 2j + -2j = 0 -4 + 1j = 0 Add '4' to each side of the equation. -4 + 4 + 1j = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 1j = 0 + 4 1j = 0 + 4 Combine like terms: 0 + 4 = 4 1j = 4 Divide each side by '1'. j = 4 Simplifying j = 4
| 15+0.17x=40 | | 35=2y+9 | | 21xy-7x= | | -9/10b=-18 | | x+250y=1000 | | y+6.2=-2.4 | | (2x-6)(x-1)=0 | | (-10-5x)-1=14 | | -(4a-3b+5c)= | | x=b-8/a-1 | | factorx^2+10x-24=0 | | 7k+3=5 | | Y=9-2x+3 | | 5=-16x^2+45x+6 | | Y=5x^2-7x-6 | | 7w-5=-4(w-7) | | 12a-9=3 | | ln(x)-ln(5)=5 | | -32=-8u | | log(4x+24)=3 | | 5=16/x | | (3x+14)=(7x) | | 63=25x | | -28x^2-32x+16=0 | | -x^2+4.5x+1=0 | | 5/1=16/x | | x^2=420 | | 2(k+7)=32 | | 2x+5x-10+3=6x-7.2+x | | 4A=(B+b)*h | | 4x^3+8x^2+5x=0 | | -8x-2x=-56+48 |